REVIEWING POVERTY IN INDONESIA: KARL MARX'S VIEW OF RELIGION IS AN OPIUM - Lela Saputri, Pungky; Gunaryo, Achmad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
This study aims to review poverty through Karl Marx's view of religion as an opium. The method used in this research is qualitative with library studies approach. The current globalization and the order of capitalism occurred in Indonesia, certainly enriching the strong and impoverishing the weak. The role of religion in Indonesia in dealing with poverty is not much different from the reality faced by Karl Marx. Karl Marx thought of religion as an impediment to social change. This thought is reflected in his own assertion that religion is the opium of society. In Indonesia, religion only directs people to accept poverty and entertain them by inviting them to preach to the afterlife.